2017
DOI: 10.1186/s12998-017-0155-x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking low back pain in adolescent idiopathic scoliosis: a prospective cohort study protocol

Abstract: BackgroundNumerous methodological limitations have constrained the findings of previous studies that have examined the prevalence of low back pain in adolescents with idiopathic scoliosis. This article presents a study protocol that has been designed to address the shortcomings of prior research in this area. In addition, it will establish the level of disease burden associated with acute, recurrent, and chronic low back pain in adolescents with idiopathic scoliosis.MethodsThis study will involve a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Infantile, juvenile, or adolescent idiopathic scoliosis (AIS) is classified based on the age at which it is first recognized [1][2]. AIS affects children over the age of 10, up to skeletal maturity, and with a prevalence of 0.47% to 5.2%, it is the most common spinal deformity that develops in otherwise healthy children [2][3][4][5][6][7]. Moreover, AIS has a female predominance with a 1.5:1 to 3:1 ratio [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infantile, juvenile, or adolescent idiopathic scoliosis (AIS) is classified based on the age at which it is first recognized [1][2]. AIS affects children over the age of 10, up to skeletal maturity, and with a prevalence of 0.47% to 5.2%, it is the most common spinal deformity that develops in otherwise healthy children [2][3][4][5][6][7]. Moreover, AIS has a female predominance with a 1.5:1 to 3:1 ratio [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that back pain is a widespread complaint associated with AIS, ranging from a 20% to 85% prevalence [2][3][4][5][6][11][12]. Regarding the intensity of the pain, it has been observed that higher levels of deformity are associated with more pain [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of disability-adjusted life years, LBP incurs a substantial burden over other health-related conditions [3,4]. Although LBP is more common in patients above 65 years old [5,6], it can start as early as in the late teenage years [7]. It is classified as the most expensive healthcare treatment, ranging between 12 to 90 billion dollars in the United States alone [8] and above 500 million pounds in the United Kingdom according to the nice guideline [9].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ]. Low back pain involves the occurrence of pain in the space between the rib cage and gluteal fold and can also be defined as acute, recurrent, or chronic episodes [ 3 ]. Low back pain symptoms can derive from many anatomic sources, such as nerve roots, muscles, fascial structures, bones, joints, intervertebral discs, and organs within the abdominal cavity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%